2008
DOI: 10.1016/s1976-1317(08)60042-0
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence and Abuse Against Nurses in Hospitals in Iran

Abstract: The findings showed a noticeable trend of a rising number of assaults against nurses. The findings of this study may help hospital staff and nurses to avoid, reduce and control violence and abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 20 publications
11
74
1
3
Order By: Relevance
“…Our study shows that staff nurses had experienced more violence than ANMs which is paradoxical with the findings of a study conducted in Iran and Jordan, which showed that nurses with lower position were exposed to workplace violence. 7,23 The difference in findings might be due to variation in age and working experience between nurses and ANMs. Unlike with this study results, a study conducted in Southern Thailand 19 showed that nurses working in rotating shifts experienced more violence than nurses in fixed shifts.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Our study shows that staff nurses had experienced more violence than ANMs which is paradoxical with the findings of a study conducted in Iran and Jordan, which showed that nurses with lower position were exposed to workplace violence. 7,23 The difference in findings might be due to variation in age and working experience between nurses and ANMs. Unlike with this study results, a study conducted in Southern Thailand 19 showed that nurses working in rotating shifts experienced more violence than nurses in fixed shifts.…”
Section: Resultsmentioning
confidence: 96%
“…Studies in Iran, Southern Thailand, and Palestine support the findings of our study. 7,10,15,21,22 The reason behind this could be that the nurses with less experience may commit mistakes and also they may lack sound communication skills. Our study shows that staff nurses had experienced more violence than ANMs which is paradoxical with the findings of a study conducted in Iran and Jordan, which showed that nurses with lower position were exposed to workplace violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…간호사의 대부분이 여성이어 서 성별에 따른 폭력을 비교하기 어려운 경우도 있으나 [12], 성별에 따른 차이 유무에 대한 다양한 연구결과가 보고되고 있다 [21][22][23][24][25]. 여성에 대한 폭력은 심각한 사회적 문제로서, 성 별에 기반한 권력관계와 성적인 특성, 자아정체성의 영향을 받는 복합적인 현상으로 파악되고 있다 [2,5]. …”
Section: 관계 갈등에 초점을 두고 동료간호사들로부터 발생할 수 있는 폭력에 대한 연구에서는 신체적 위협보다는 주로 간unclassified